2022
DOI: 10.35516/jjps.v15i1.299
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Investigation of Sanchezia nobilis Leaves Extract

Abstract: The project work was designed to investigate the phytochemical and selected pharmacological activities (anti-diarrheal, analgesic, neuropharmacological behavior and anthelmintic) of leaves of Sanchezia nobilis. Hook. F. (Family: Acanthaceae). From its phytochemical analysis we found the presence of reducing sugar, combined reducing sugar, phenolic compounds, tannins, flavonoids, carbohydrates, gums, steroids, alkaloids, glycosides and terpenoids. In vivo antidiarrheal activity was substantiated by prolongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…This secondary stage involves -666 -the coagulation cascade, which consists of three distinct but interconnected pathways: the intrinsic, extrinsic, and common pathways. 21 Subsequently, we measured CAI activity. In our diuretic and urinary electrolyte analysis test, we found that the F. indica ethyl acetate fraction at 500 mg/kg doses exhibited the best diuretic activity, and a diuretic index exceeding 1.5 indicates a good diuretic effect.…”
Section: Discussionmentioning
confidence: 99%
“…This secondary stage involves -666 -the coagulation cascade, which consists of three distinct but interconnected pathways: the intrinsic, extrinsic, and common pathways. 21 Subsequently, we measured CAI activity. In our diuretic and urinary electrolyte analysis test, we found that the F. indica ethyl acetate fraction at 500 mg/kg doses exhibited the best diuretic activity, and a diuretic index exceeding 1.5 indicates a good diuretic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the Anthelmintic Effect. In vivo anthelmintic effect of SCE was assessed by a method described by Paul et al [15]. From the freshly slaughtered oxen in local abattoirs in Khulna, live P. cervi were collected.…”
Section: Evaluation Of Neuropharmacological Behavior By Open-field Mo...mentioning
confidence: 99%
“…Although considered a safe option, SSRIs have many limitations: they are effective only in 50% of cases, they could lead to weight gain or sexual impairment, and they take up to two weeks to exert a clinically acceptable effect (12,13). Therefore, herbs with psychotropic effects are gaining wide attention due to their high safety profile, minimal drug interactions, and negligible addictive potential (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%